2008
DOI: 10.1002/jssc.200700361
|View full text |Cite
|
Sign up to set email alerts
|

GC‐MS analysis of organic compounds in wastewater and sewage sludge

Abstract: A multimethod based on liquid-liquid extraction and solid-liquid extraction for the analysis of persistent organic pollutants in water and sludge from sewage treatment plants has been established. Traces of 22 organic compounds used in industry and personal care products (PCPs) were analyzed by GC/MS. The LODs for the analytes were less than 2.3 ng/L for wastewater and 31 microg/kg (dry weight matter) for sewage sludge. Satisfactory recoveries (70-130%) were achieved. The validated method permits the analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Although partial elimination in STPs has been reported for nitro as well as for polycyclic musks, little information is available for macrocyclic musks. Moreover, no data have been published for alicyclic musks (Ligon et al, 2008;Lopez-Nogueroles et al, 2013;Vallecillos et al, 2015a). Moreover, some synthetic musks can be transformed in STPs as well as in biota, being transformation products even more problematic than the parent musks , in terms of potential toxicity.…”
Section: Introductionmentioning
confidence: 95%
“…Although partial elimination in STPs has been reported for nitro as well as for polycyclic musks, little information is available for macrocyclic musks. Moreover, no data have been published for alicyclic musks (Ligon et al, 2008;Lopez-Nogueroles et al, 2013;Vallecillos et al, 2015a). Moreover, some synthetic musks can be transformed in STPs as well as in biota, being transformation products even more problematic than the parent musks , in terms of potential toxicity.…”
Section: Introductionmentioning
confidence: 95%
“…The hike in usage caused significant issues revolving around accidental poisoning from unfitting use and pharmaceutical loading [3]. Despite being an important matter of concern, the disposal of unused medicines has long been an unspoken issue worldwide [4,5]. About 30 years ago, pharmaceuticals consisting of organic compounds that disturb human health and marine ecosystems were identified in the environment [4,[6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Despite being an important matter of concern, the disposal of unused medicines has long been an unspoken issue worldwide [4,5]. About 30 years ago, pharmaceuticals consisting of organic compounds that disturb human health and marine ecosystems were identified in the environment [4,[6][7][8][9][10][11]. To date, a large number of studies showed the presence of pharmaceuticals in water bodies such as in groundwater [12,13], surface water [8,12], aquatic and coastline environments [13], and recipient water, sludge, and wastewater [14].…”
Section: Introductionmentioning
confidence: 99%
“…Other analytical techniques such as stir‐bar sorptive extraction , microextraction by packed sorbents , and membrane‐assisted solvent extraction (MASE) were developed and validated to quantify SMC in filtered or centrifuged water samples. But for a considerably high number of publications using methods presented previously such as membrane‐assisted liquid–liquid extraction , microextraction by packed sorbent , microwave‐assisted headspace solid‐phase microextraction , SPME , dispersive liquid–liquid microextraction , single‐drop microextraction , SPE or even LLE , it is difficult to point out precisely if the samples were filtered or not and if they are, thus, representative of the natural system in study.…”
Section: Introductionmentioning
confidence: 99%